Science and society: a dialogue without communicators? - Nico Pitrelli (JCOM: Journal of Science Communication, 2008)
To give a good public speech is art; but definitely more difficult is to organize a productive exchange of points of views between scientists, experts, non-experts and policy-makers on controversial issues such as a scenario workshop or a consensus conference. Many skills and a deep knowledge both of the topic and of the methodology are required. But this is the future of science communication, a field where the dialogical model will impose new and complex formats of communication and a new sensibility, using also the most traditional media. But are science communicators prepared for that? What is the state of the art of science communicator training?